Concussion among female athletes in Iceland : stress, depression, anxiety and quality of life - Silja Runólfsdóttir 1990- (2019)
Objective: To examine the relationship between self-reported concussion history and stress, depression, anxiety and quality of life among Icelandic female athletes. Method: Participants in the study were 508 Icelandic female athletes, aged 18-45 (M = 26.99, SD = 7.14), that had or were currently training and competing in the two top leagues in basketball, soccer and handball, in the top league in ice-hockey and in national tournaments in mixed martial arts, taekwondo, karate and boxing. Participants completed an online questionnaire regarding their age, sport and concussion history before answering standard mental health scales concerning stress (PSS), depression (PHQ-9), anxiety (GAD-7) and quality of life (QOLS). Results: Female athletes with a history of one or more concussions scored significantly higher on PHQ-9 and with two or more on PSS and GAD-7 than those reporting no concussion history. Scores on the QOLS were not significantly different between the groups. Female athletes having sustained a concussion were 3.9 times more likely to score above clinical cut-off on PHQ-9 and 2.3 times more likely to score above clinical cut-off on GAD-7 than those with no history of concussion. Number of concussions sustained significantly predicted scores on PSS, PHQ-9, GAD-7 and QOLS. Conclusion: Results indicate that Icelandic female athletes with a history of concussion feel worse than those with no history of concussion and the higher number of concussions sustained, the worse they feel. Keywords: Concussion, athletes, stress, depression, anxiety, quality of life